Charting pathways to gender equality reflections and challenges - Cenwor; CENWOR (Organization : Sri Lanka) (Colombo Vijitha Yapa Publications,=, 2010)
Contributed articles on feminism and women's rights in Sri Lanka.
"Copyright: CENWOR"--p. facing t.p.
Keywords: Feminism -- Sri Lanka; Women's rights -- Sri Lanka